2017
DOI: 10.1016/j.zemedi.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Higher order chromatin structures are taking shape

Abstract: ForumHigher order chromatin structures are taking shape Chromatinstrukturen höherer Ordnung nehmen Gestalt an.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Recent advances have shown that at the kilo- to megabase scale, the chromatin fiber organizes into preferentially interacting regions, referred to as Chromosomally Interacting Domains (CIDs) or Topologically Associating Domains (TADs), which for example regulate enhancer–promoter interactions and replication units through the action of cohesin and CTCF [12,13]. TADs further associate with other domains of similar properties into compartments of heterochromatin and euchromatin [14,15]. At the chromosomal level, chromosomes occupy non-overlapping territories in interphase, and compact to their highest degree as metaphase chromosomes during mitosis [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances have shown that at the kilo- to megabase scale, the chromatin fiber organizes into preferentially interacting regions, referred to as Chromosomally Interacting Domains (CIDs) or Topologically Associating Domains (TADs), which for example regulate enhancer–promoter interactions and replication units through the action of cohesin and CTCF [12,13]. TADs further associate with other domains of similar properties into compartments of heterochromatin and euchromatin [14,15]. At the chromosomal level, chromosomes occupy non-overlapping territories in interphase, and compact to their highest degree as metaphase chromosomes during mitosis [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Eukaryotic genomes are highly organized and division into euchromatic and heterochromatic compartments is crucial for the correct execution of gene expression programs, for establishment of chromosomal structures such as telomeres and centromeres and for protection of the genome from parasitic genetic elements (Grewal and Jia 2007;Schalch 2017).…”
mentioning
confidence: 99%